2020
DOI: 10.1158/1078-0432.ccr-20-3182
|View full text |Cite
|
Sign up to set email alerts
|

Iron Induces Cell Death and Strengthens the Efficacy of Antiandrogen Therapy in Prostate Cancer Models

Abstract: Purpose: In search of novel strategies to improve the outcome of advanced prostate cancer, we considered that prostate cancer cells rearrange iron homeostasis, favoring iron uptake and proliferation. We exploited this adaptation by exposing prostate cancer preclinical models to high-dose iron to induce toxicity and disrupt adaptation to androgen starvation. Experimental Design: We analyzed markers of cell viability and mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 38 publications
0
49
2
Order By: Relevance
“…Metabolic iron feedback between prostate cancer cells and macrophages provides a putative connection between macrophage infiltration and tumor iron dysfunction observed in prostate cancer. Prostate cancer cells are highly dependent on iron for their proliferation ( 57 ). In this iron addicted state, they exhibit a low FPN high TfR phenotype and synthesize hepcidin to induce neighboring tissue iron retention to support their cellular program.…”
Section: Iron Metabolism and Macrophages In Cancermentioning
confidence: 99%
“…Metabolic iron feedback between prostate cancer cells and macrophages provides a putative connection between macrophage infiltration and tumor iron dysfunction observed in prostate cancer. Prostate cancer cells are highly dependent on iron for their proliferation ( 57 ). In this iron addicted state, they exhibit a low FPN high TfR phenotype and synthesize hepcidin to induce neighboring tissue iron retention to support their cellular program.…”
Section: Iron Metabolism and Macrophages In Cancermentioning
confidence: 99%
“…Ferrous iron contributes electrons when it reacts with hydrogen peroxide, producing hydroxyl radicals, which are ROS [ 21 , 22 ]. This process, known as the Fenton reaction, not only destroys lipids and proteins but also leads to oxidative damage to DNA, including modification of DNA bases and breakage of DNA strands [ 23 ]. Therefore, iron is both essential and potentially toxic.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that LNCaP cells were highly iron-sensitive while DU-145 and PC 3 cells were poorly iron-sensitive. The toxicity of iron mainly drives lipids to promote ferroptosis 30 .…”
Section: Discussionmentioning
confidence: 99%